Excited-State Evolution of Keto-Carotenoids after Excess Energy Excitation in the UV Region - Khan, Tuhin; Litvín, Radek; Šebelík, Václav; Polívka, Tomáš (Chemphyschem, 2021)
Carotenoids are molecules with rich photophysics that are in many biological systems involved in photoprotection. Yet, their response to excess energy excitation is only scarcely studied. Here we have explored excited state properties of three keto-carotenoids, echinenone, canthaxanthin and rhodoxanthin after excess energy excitation to a singlet state absorbing in UV. Though the basic spectral features and kinetics of S2 , hot S1 , relaxed S1 states remain unchanged upon UV excitation, the clear increase of the S* signal is observed after excess energy excitation, associated with increased S* lifetime. A multiple origin of the S* signal, originating either from specific conformations in the S1 state or from a non-equilibrated ground state, is confirmed in this work. We propose that the increased amount of energy stored in molecular vibrations, induced by the UV excitation, is the reason for the enhanced S* signal observed after UV excitation. Our data also suggest that a fraction of the UV excited state population may proceed through a non-sequential pathway, bypassing the S2 state.
Keywords: photophysics; UV radiation; ultrafast dynamics; carotenoids; excess energy excitation